ROMANTICISM IN THE POEM “ILA UMMI” BY MAHMOUD DARWISH BASED ON THE PERSPECTIVE OF JOHANN WOLFGANG VON GOETHE - Mohammad Ulil Albab Abdalah; Respati Yurisa, Penny (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This paper?uses Johann Wolfgang von Goethe's literary Romanticism to analyze traits of Romanticism in Mahmoud Darwish's